„Frank, ciągle tam jesteś?”. O listach i książkach w filmie 84 Charing Cross Road (1987) - Pławuszewski, Piotr (Przestrzenie Teorii, 2019)
Pławuszewski Piotr, „Frank, ciągle tam jesteś?”. O listach i książkach w filmie 84 Charing Cross Road (1987) [“Frank, you still there?”. On books and letters in David Jones’ 84 Charing Cross Road (1987)]. „Przestrzenie Teorii” 32. Poznań 2019, Adam Mickiewicz University Press, pp. 93–114. ISSN 1644-6763. DOI 10.14746/pt.2019.32.4. 84 Charing Cross Road (1987, dir. by David Jones) is the story of 20-year-long (1949–1969) correspondence between the American writer Helene Hanff and London antiquarian Frank Doel. The letters (edited and prepared for printing by Hanff) were published under the same title in 1970. This article is a precise analysis of the film work, particularly in the context of the two most important elements of its narrative and semantic plane (excluding the strictly historical introductory part). The first is a letter, understood mainly in its artistic function, the second, a book, both as a material object and a medium of literary content. Treating the epistolary material with ingenuity worthy of respect, the filmmakers managed to create one of the most convincing images of literary culture in the history of cinema, albeit one rather forgotten nowadays.